AGE‐modified basement membrane cooperates with Endo180 to promote epithelial cell invasiveness and decrease prostate cancer survival. Issue 4 (24th December 2014) - Rodriguez‐Teja, Mercedes; Gronau, Julian H; Breit, Claudia; Zhang, Yu Zhi; Minamidate, Ai; Caley, Matthew P; McCarthy, Afshan; Cox, Thomas R; Erler, Janine T; Gaughan, Luke; Darby, Steven; Robson, Craig; et al.
Abstract Biomechanical strain imposed by age‐related thickening of the basal lamina and augmented tissue stiffness in the prostate gland coincides with increased cancer risk. Here we hypothesized that the structural alterations in the basal lamina associated with age can induce mechanotransduction pathways in prostate epithelial cells (PECs) to promote invasiveness and cancer progression. To demonstrate this, we developed a 3D model of PEC acini in which thickening and stiffening of basal lamina matrix was induced by advanced glycation end‐product (AGE)‐dependent non‐enzymatic crosslinking of its major components, collagen IV and laminin. We used this model to demonstrate that antibody targeted blockade of CTLD2, the second of eight C‐type lectin‐like domains in Endo180 (CD280, CLEC13E, KIAA0709, MRC2, TEM9, uPARAP) that can recognize glycosylated collagens, reversed actinomyosin‐based contractility [myosin‐light chain‐2 (MLC2) phosphorylation], loss of cell polarity, loss of cell–cell junctions, luminal infiltration and basal invasion induced by AGE‐modified basal lamina matrix in PEC acini. Our in vitro results were concordant with luminal occlusion of acini in the prostate glands of adult Endo180ΔEx2–6/ΔEx2–6 mice, with constitutively exposed CTLD2 and decreased survival of men with early (non‐invasive) prostate cancer with high epithelial Endo180 expression and levels of AGE. These findings indicate that AGE‐dependent modification of the basal lamina induces invasive behaviour in non‐transformed PECs via a molecular mechanism linked to cancer progression. This study provides a rationale for targeting CTLD2 in Endo180 in prostate cancer and other pathologies in which increased basal lamina thickness and tissue stiffness are driving factors. © 2014 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of Pathological Society of Great Britain and Ireland.